Tinjauan Yuridis tentang Penetapan Sebagai Saksi Pelaku yang Bekerja Sama (Justice Collaborator) pada Kasus Tindak Pidana Korupsi di Indonesia - See, Benedictus Renny (Jurnal Hukum Caraka Justitia, 2024)
The purpose of this study is to analyze the laws and regulations governing the legal position and role of justice collaborators, especially regarding the criteria for a person to be designated as a justice collaborator and what is the limit of legal reduction for a justice collaborator. This research is a normative juridical research that is descriptive and analytical, using a legislative approach related to the role and position of justice collaborators in corruption crimes. Data is obtained through document studies and analyzed using qualitative normative methods.Based on the results of the research, it is known that the determination of a person to be able to serve as a Justice Collaborator has not been expressly regulated in the Criminal Code or laws and regulations governing corruption crimes and there are no rules governing the amount of sentence reduction that can be received by a justice collaborator. The suggestion of this research is the need for a special regulation on justice collaborators which regulates the determination as a cooperating whistleblower (justice collaborator), especially about the definition of “Main Perpetrator” and the need for a clear determination of the amount of sentence reduction that can be given to a justice collaborator as a guideline for law enforcers in determining a person as a justice collaborator in a corruption case.